2015
DOI: 10.1007/s10439-015-1411-7
|View full text |Cite
|
Sign up to set email alerts
|

Solid Tumor Embolotherapy in Hepatic Arteries with an Anti-reflux Catheter System

Abstract: Unresectable hepatoma accounts for the majority of malignant liver tumor cases for which embolization therapy is considered a viable treatment option. However, the potential risk of aberrant particle deposition in non-target regions could cause severe side-effects, alongside diminished efficacy. A computational model has been developed to analyze the particle-hemodynamics before and after deployment of an FDA-approved anti-reflux catheter. The catheter features a retractable, porous cone-like tip designed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The authors hypothesize that the MVI catheters demonstrated greater on-target microsphere deposition within the tumor and increased tumor percentage necrosis through three mechanisms. First, the expandable tip in the MVI catheter acts as a one-way valve that enables operators to preferentially target tumor tissue by eliminating reflux [23]. During TACE performed with EH microcatheters, the infusion is terminated when stasis is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesize that the MVI catheters demonstrated greater on-target microsphere deposition within the tumor and increased tumor percentage necrosis through three mechanisms. First, the expandable tip in the MVI catheter acts as a one-way valve that enables operators to preferentially target tumor tissue by eliminating reflux [23]. During TACE performed with EH microcatheters, the infusion is terminated when stasis is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…A planar model of the human liver vasculature was also recently developed by Xu et al to study quantitative endpoints during embolization. Channel diameter ranged from 6 mm (celiac artery) down to 1 mm arterial branches, and physiological values of static pressure (70–150 mmHg) and flow rate (200–500 mL min −1 through the whole liver) were replicated using a homogeneous non‐Newtonian fluid.…”
Section: Flow Behavior and Occlusion Performance Of Embolic Devicesmentioning
confidence: 99%
“…Therefore, a possible explanation to the similar incidence of increased blood pressure in 2 groups might be that the chemotherapeutics and embolic agents, namely the microbeads, were of no difference between 2 groups. [ 22 , 23 ]…”
Section: Discussionmentioning
confidence: 99%